Careers and mismatch for college graduates: College and non-college jobs - Andrew Agopsowicz; Chris Robinson; Ralph Stinebrickner; Todd R. Stinebrickner (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
A large literature studies the wage consequences of over-education in the sense of a worker, by some measure, having a higher level of education than is required for the job. We use unique new data to reexamine the common interpretation that initial over-education represents a harmful type of mismatch that arises due to information induced frictions. We contrast this with the alternative that college graduates are heterogeneous with respect to their human capital and that the labor market is appropriately allocating them to jobs, even when many are observed starting in jobs that do not require a college degree.
Keywords: 330